Brazil between global recognition and neutrality over the Russian war against Ukraine - Tabosa Clarissa (Journal of Regional Security, 2023)
This contribution investigates what explains Brazil's neutrality narrative regarding the Russian war against Ukraine. Brazil's position can be seen as a consequence of the economic interests of Brazilian agrobusiness, but mainly due to its historical tradition of diplomatic neutrality. However, neutrality seems to clash with Brazil's self-conceptualization as being a relevant player at the international level, especially since the 2000s. I show how this identitarian clash has led to an attempt to move from "neutrality" to an "impartiality" discourse, and argue that Brazil might partially align with the West to meet core strategic foreign policy goals.